Entrepreneurship and Institutions - Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2007)
In this paper entrepreneurs are defined as agents who bring about economic change by combining their own effort with other factors of production in search of economic rents. The institutional setup is argued to determine both the supply and direction of entrepreneurial activity. Four key institutions are explored more closely: property rights protection, savings policies, taxation and the regulation of labor markets. Institutions have far-reaching effects on entrepreneurship, and they largely determine whether or not entrepreneurial activity will be socially productive. Due to the responsiveness of entrepreneurship to the institutional setup it is maintained that in-depth analyses of specific institutions are required in order to further our understanding of the determinants of entrepreneurial behavior and the economic effects of entrepreneurship. The paper also demonstrates that it is problematic to use self-employment as an empirical proxy for productive entrepreneurship.
Keywords: H32; L25; L50; M13; O31; P14; 330; Entrepreneurship; Industrial policy; Innovation; Institutions; Labor security; Property rights; Regulation; Self-employment; Tax policy; Entrepreneurship-Ansatz; Institutionelle Infrastruktur; Eigentumsrecht; Steuerpolitik; Sparförderung; Arbeitsmarktpolitik; Theorie